Of salt and shore - Schaap, Annet (Charlesbridge, 2022)
Young Lampie, the lighthouse keeper's daughter, is in charge of lighting the lantern to keep ships away from the rocks; but on a story night she runs out of matches and tragedy strikes--a ship smashes into the rocks. Lampie is taken away from her father and sent to work as a maid at the Admiral's Black House where a rumored monster lurks. There Lampie embarks on a magical adventure fraught with mermaids and pirates; an adventure that will force her to fight for her friends and herself.